Model predictive control-based control algorithm for a target-chaser maneuvering situation. (17th November 2021) - Gilimalage, A. S. M.; Kimura, S.
Abstract : The utilization of space for human activities has increased steadily over the past several decades. In parallel, space debris has also grown at an alarming rate, posing risks to space missions and establishing debris removal as an aspiration in the current space industry. These objects can orbit at arbitrary rotational speeds in different planes. In this paper, a model predictive control-based algorithm is developed for a target-chaser rendezvous situation to optimize fuel consumption while considering thruster constraints and memory usage. A performance comparison is conducted with several conventional controllers to validate the effectiveness of the algorithm using computer simulations. GRAPHICAL ABSTRACT: UF0001